Monument at Graignemanagh Co. Kilkenny - Grose, Daniel, approximately 1766-1838 (1792)
Drawing of the Knight of Duiske in Duiske Abbey, Graignemanagh, County Kilkenny, Ireland. This is a fourteenth century high-relief carving of a knight in chain mail reaching for his sword.